YOO I NEED THIS RIGHT NOW!!
What is the difference of
[tex]( \frac{3}{4} x - \frac{2}{3} ) - ( - \frac{5}{6} + 2x)[/tex]
?
[tex] - \frac{5}{4} x + \frac{1}{6} [/tex]
[tex] - \frac{5}{4} x - \frac{1}{6} [/tex]
[tex] \frac{11}{4} x + \frac{1}{6} [/tex]
[tex] \frac{11}{4} x - \frac{1}{6} [/tex]

Respuesta :

Answer:

The first option: -5/4x + 1/6.

Step-by-step explanation:

(3/4x - 2/3) - (-5/6 + 2x)

= (3/4x - 2/3) + 5/6 - 2x

= 3/4x - 2x - 2/3 + 5/6

= 3/4x - 8/4x - 4/6 + 5/6

= -5/4x + 1/6

So, the first option: -5/4x + 1/6.

Hope this helps!